(untitled) (Medico Legal Update, 2020)
In developing nations, the adolescent group is progressively exposed to health issues and young girls are increasingly weak due to anemia. An observational study was conducted to assess the prevalence of anemia among the adolescent girls in a selected college in Kanchipuram. The objectives were to assess the sociodemographic variables of the adolescent girls, to assess the prevalence of anemia among the adolescent girls and to associate the prevalence of anemia and the socio-demographic variables of the adolescent girls. The cross sectional design was used to conduct the study. The setting of the study was a selected Allied Health Science college in Chennai. Adolescents in the age group of 17 to 19 years were selected as samples for the study. The convenience sample technique was used to select the samples. The sample size was 32. The results showed that 16 (50.0%) of the participants belong to the age 17 years and 18 years equally and the majority of the study participants 27 (84.0%) belong to nuclear family and 05 (16.0%) of the population belong to joint family and the 08 (25.0%) of the study participants were vegetarian and 24 (75.0%) of them were non vegetarian. The level of hemoglobin showed that majority of the study participants 22 (56.0%) suffer low hemoglobin level.